(untitled) (Journal of Hama University, 2022)
This study aimed to find out the role of technical analysis in making an investment decision from the point of view of clients, specifically by clients dealing with commercial banks . To achieve the objectives of the study, a special questionnaire was developed and distributed to clients wishing to invest in commercial banks in Lattakia Governorate. For data analysis and hypothesis testing, a set of statistical tests based on the statistical program spas was used.Based on this, the study concluded the following. The results showed that the importance of technical analysis in commercial banks from the point of view of customers in banks came to a high degree, which indicates a clear tendency for customers in banks to realize the importance and usefulness of technical analysis in order to make a rational and optimal investment decision. The study made several recommendations to improve the level of investment decision provided through full and comprehensive knowledge of technical analysis and interest in it to a great extent.